Functional Features of Mechanisms for State Regulation of Innovational Development of Commerce and Industrial Sphere of Economy of Ukraine - Gibadullin , Oleksiy (Pressing Problems of Public Administration, 2019)
The paper considers the issues related to the speci city of the de nition and functioning of the mechanisms for the state regulation of the innovational development of the commercial and industrial sphere of the Ukrainian economy. Also, the combination of the mechanisms, methods and tools for the state regulation of that sphere has been generalized. The currently recognized point of view describes enterprises of that kind and the mechanisms for the state regulation of their activity and innovational development within the structures of the existing industrial classi cation, neglecting the commercial and industrial sphere as a separate signi cant unit of the economy. When forming the mechanisms for the state regulation of the innovational development of the commerce and industrial sphere of the economy of Ukraine, it is necessary to take into account the speci city of businesses’ operation in commerce and industry, the features of their sales and commodity markets, their possibilities of establishing and strengthening of international economic ties, and their basic goals. Evaluating the current functional condition of the mechanisms for the state regulation concerning the enterprises in the commercial and industrial sphere of the economy of Ukraine, one can note a practically total lack of attention on behalf of the state towards businesses of that important sphere. The state regulation lies in establishing by the state of certain general rules of conduct (activity) for the participants of social relations, and their correction depending on the changing conditions. Based on the generally recognized classi cation of the mechanism for state regulation, the author emphasizes the following mechanisms for the state regulation of the innovational development of the commercial and industrial sphere of the Ukrainian economy: normative and legal, administrative, economic, social, information, which, in turn, are integrated into a complex mechanism for the state regulation of the innovational development of the commercial and industrial sphere of the economy of Ukraine. Businesses of the commercial and industrial sphere of the domestic economy possess a profound scienti c, technological, and economic potential; they have an opportunity to enter the international market with their own products. Due to their speci c features and the nature of their economic and production relations, they understand the laws of the market operation. The signicance of these businesses for the national economy and their impact on the formation of the GDP can hardly be overestimated. Therefore, the issue of the state regulation of the innovational development of businesses in the said sphere is going to gain topicality with every year to come.